(untitled) (Medical Forum Monthly, 2024)
Objective: To find the prescription pattern of antihypertensive drugs in the department of Nephrology Khyber Teaching Hospital Peshawar Study Design: Observational / cross sectional study. Place and Duration of Study: This study was conducted at the outpatient department of nephrology Khyber Teaching Hospital Peshawar from January 2018 to March 2018. Materials and Methods: 200 patients suffering from hypertension were included in the study. We examined the frequency and proportion of various antihypertensive drugs as mono therapy, combination therapy and fixed drug combinations (FDCs). Results: Most frequently prescribed antihypertensive drugs were CCBs (65%) followed by diuretics (54%), beta blockers (50.5%), ARBs (26%) and ACEIs (21%) respectively. 57.5% were using two drugs and most commonly used FDCs was diuretics with ACEI. Conclusion: Calcium channel blockers are mostly prescribed while alpha blockers are the least prescribed antihypertensives drugs.